Research Paper: Evaluation of the Activity and Dimensions Changes of the Skeletal Muscles During Different Activities: A Systematic Review - Sharareh Kian Bostanabad (Journal of Modern Rehabilitation, 2017)
Introduction: The knowledge of muscle function during various activities may affect medical and physical treatments. Recently, ultrasound has been used to assess the activity of skeletal muscles. The relationship between ultrasound data with Electromyography (EMG) and dynamometry has been evaluated in numerous articles. This study aims to review the papers in this topic. Materials and Methods: By searching the papers in Google Scholar, ScienceDirect, PubMed and PEDro (Physiotherapy evidence database) and then checking the papers referenced to found studies, 28 related papers were chosen and evaluated. Results: Regarding data recording methods in 28 papers, ultrasound and EMG had been used in 5 papers, ultrasound and dynamometry in 13 cases and all three methods in 10 papers. Conclusion: Although the relationship between EMG and ultrasound data have been examined in many studies, there are shortages and in some cases lack of mathematical equations and predictive models representing the majority of skeletal muscles. Therefore, quantifying the relationship between ultrasound data with EMG and dynamometry and providing predictive models can be useful in using ultrasound (which is a noninvasive, cheap and available method) in both research and clinical fields.